Pigments of aminophenoxazinones and viridomycins produced by termite-associated Streptomyces tanashiensis BYF-112 - Zhang, Shuxiang; Wu, Jun; Jiang, Zhou; Zhang, Le; Song, Tao; Liu, Xinhua; Yin, Caiping; Zhang, Yinglao (Frontiers in Microbiology, 2023)
Abstract: Termite-associated Streptomyces tanashiensis BYF-112 was found as a potential source for yellow and green pigments, which were stable under the tested temperature, light and metal ions. Eight metabolites (1-8), including four new natural yellow pigments aminophenoxazinones (1-4), and two rarely iron dependent green pigments viridomycin A and F (9-10) were isolated from BYF-112 cultured in YMS and YMS treated with FeSO4, respectively. The metabolites 2-4 displayed a significant safety performance on the normal liver cell line L-02, while the metabolite 1 showed weak cytotoxicity against the L-02 and several cancer cells. Especially, in the filter paper disc tests, the compound 1 possessed strong antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) with the zone of inhibition (ZOI) of 15.3 mm, which was equal to that of referenced levofloxacin (ZOI = 15.2 mm). And the metabolite 1 also showed moderate antibacterial activities against Micrococcus teragenus and S. aureus, with the ZOI values of 15.3 and 17.2 mm. In addition, by the minimum inhibitory concentration (MIC) assay, the compound 1 displayed potential antibacterial activities against M. teragenus, S. aureus and MRSA, with the MIC values of 12.5, 12.5 and 25.0 μg/mL, respectively. The present results indicate that BYF-112 may be a promising source for safe and bioactive pigments, which can be used for further development and industrial applications. Key words: Streptomyces tanashiensis BYF-112, Natural pigments, Aminophenoxazinones, Viridomycins, Cytotoxic and antibacterial activities.